Expression of Endothelin-1, Endothelin Receptor-A, and Endothelin Receptor-B in facial melasma compared to adjacent skin - da Silva, Carolina Nunhez [UNESP]; Miot, Hélio Amante [UNESP]; Grassi, Tony Fernando [UNESP]; Dias-Melício, Luciane Alarcão [UNESP]; Santos, Leandro [UNESP]; Espósito, Ana Cláudia Cavalcante [UNESP] (Taylor & Francis, 2023)
Background/Objectives: Although melasma is highly prevalent, its pathogenesis is not yet fully understood. In the skin, endothelin-1 (ET-1) is primarily produced by keratinocytes in response to UVB exposure, which is mediated by an increase in IL-1α or reactive oxygen species. ET-1 plays a role in melanogenesis by binding to specific receptor B (ERB) or receptor A (ERA). However, the expression of ET-1, ERA, and ERB in melasma has not been systematically investigated. The objective of this study was to evaluate the expression of ET-1, ERA, and ERB in facial melasma compared to the adjacent unaffected skin. Methods: Cross-sectional study, with 40 skin samples (20: facial melasma; 20: adjacent unaffected skin) from women with facial melasma without treatment for 30 days except for sunscreen. A triple staining immunofluorescence technique was performed for anti-vimentin, DAPI, plus one of the following antibodies: (a) anti-ET1, (b) anti-ERA; (c) anti-ERB. Interfollicular areas on the slides of each topography (melasma; unaffected skin) were photographed in triplicate under confocal laser microscopy. The mean staining intensities of the image histograms (0–255 pixels intensity) were estimated for different types of cells (suprabasal keratinocytes, basal layer, and upper dermis) and were blindly compared between topographies. Results: The mean (SD) age of the participants was 44.9 (9.2). The expression of ET-1 was increased in the whole epidermis with melasma when compared to the adjacent skin, being 32.8% (CI95% 14.7%–52.6%) higher in the spinous layer (p=0.013), 30.4% (CI95% 13.7%–47.9%) higher in the basal layer (p=0.014), and 29.7% (CI95% 11.4%–49.7%) higher in the melanocytes (p=0.006). There was no noticeable expression of ET-1 within the cells on the upper dermis. Neither ERA nor ERB resulted in differential epidermal expression between melasma and unaffected skin (p≥0.1). Conclusion: ET-1 is expressed more intensely on the epidermis from the skin with facial melasma compared to the unaffected adjacent skin.
Keywords: endothelin receptor-A; endothelin receptor-B; endothelin-1; immunofluorescence technique; melasma